4-Methyl-N-(3-methylphenyl)pyridin-2-amine - Fairuz, Z.A.; Aiyub, Z.; Abdullah, Z.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
The title amine, C13H14N2, is twisted with a dihedral angle between the rings of 60.07 (9)°. The amine N-H group and pyridine N atom are syn allowing for the formation of centrosymmetric eight-membered {...HNCN}2 synthons via N-H...N hydrogen bonds. The two-molecule aggregates are sustained in the three-dimensional crystal packing via C-H...[pi] and [pi]-[pi] interactions [centroid-centroid distance for pyridyl rings = 3.7535 (12) Å]